The Effect of Extract of Internal Layer of Quercus(Oak)Fruit in Contraction of Vaginal Muscles in Women with Vaginal Relaxation - N Lorzadeh; F Sepavand; M Solimaninezhad; N Kazemirad (Institue of Medicinal Plants, ACECR, 2016)
Background: The Quercus (oak) fruit and especially the internal layer of the fruit (jaft) is rich in tannin and due to its astringent effects on the smooth muscles. Objective: We decided to evaluate this effect of extract of Oak Gall for vaginal tightening and rejuvenation in women with vaginal relaxation Methods: This double blind clinical trial was performed on women with vaginal relaxation at Asali Hospital in Khorramabad from May to October 2012. The participants were divided into 4 groups of 30 patients who were age-matched. Then, an extract of Oak Gall in specified concentrations (1.5%, 2% and 2.5% jells) were administered to each intervention group. Finally, the obtained data were analyzed with using SPSS software version 19. Results: The evaluation of mean scores showed that sense of sexual satisfaction and orgasm, sense of vaginal tightness during intercourse, sense of vaginal lubrication was significantly improved in patients in intervention group. Also other parameters including urinary incontinence, sense of vaginal mass exit, lack of orgasm, sense of air outflow during intercourse, sense of calmness after sex and loss of libido were significantly reduced in the group of patients who received jell 2.5% compared to other groups (P< 0.0001). Conclusion: Our findings showed that using topical jell of Oak Gall not only is associated with contracting effects, but also improves vaginal lubrication and reduces its dryness.